Use of High Frequency GNSS sensors in Dynamic Motions - Dindar, Ahmet Anıl; Gülal, Engin; Gürkan, Koray; Akpınar, Burak; GÜRKAN, GÜRAY; ÖNEN, YUSUF HATAY (My University, 2014)
Monitoring the engineered structures is becoming more vital in terms of reliable design of new and assessment of existing structures. As technological capabilities of the modern sensing instruments develop, different types of sensors have been in use as a part of monitoring systems. For the last two decades, the geosensors those are part Global Navigation Satellite Systems (GNSS) have rapidly gained popularity in studies such as crustal deformations and long-period structural systems (i.e. bridges, high-rises). GNSS system is indeed combination of GPS and GLONASS satellite constellations those were established by the USA and Russian governments, respectively. Due to its huge potential in scientific researches in addition to navigation, there have been several attempts to establish or improve satellite constellations such as Galileo by EU countries, Compass by China and IRNSS by India. Turkish Continuously Operating Reference Station (CORS-TR) network system has significantly improved the observation tolerances of the geosensors in scientific researchers. Hence, the studies aiming to give a better understanding in the use of GNSS sensors in monitoring the dynamic motions of the observation points either on the ground or on the top of a building is extremely important for near future. The results presented here have been acquired as a part of research project funded by Istanbul Kultur University in 2013 summer. The current study used a single-axis shake table for creating harmonic and random motions and the combination of LVDT, three-axis accelerometers and a GNSS receiver those measure at 50Hz, 110Hz and 100Hz, respectively. The synchronization of the data has been accomplished using GPS-based satellite clocks embedded to the sensors. The corrections of the GNSS receiver measurements were taken with respect to classical base station at 5km and CORS-TR networks. Very interesting results found in the comparison of the dynamic motion characteristics and the GNSS correction sources.